2010
DOI: 10.1111/j.1365-2958.2009.07005.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor AP2‐Sp and its target genes in malarial sporozoites

Abstract: SummaryThe malarial sporozoite is the stage that infects the liver, and genes expressed in this stage are potential targets for vaccine development. Here, we demonstrate that specific gene expression in this stage is regulated by an AP2-related transcription factor, designated AP2-Sp (APETALA2 in sporozoites), that is expressed from the late oocyst to the salivary gland sporozoite. Disruption of the AP2-Sp gene did not affect parasite replication in the erythrocyte but resulted in loss of sporozoite formation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
201
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(216 citation statements)
references
References 16 publications
14
201
0
1
Order By: Relevance
“…Luciferase assays were performed by using the dual luciferase reporter assay system (Promega) according to the manufacturer's protocol. Briefly, 10 μL of infected blood was harvested from the tail and subjected to erythrocyte lysis in 0.85% NH 4 Cl. The remaining cells were lysed in 50 μL of 1× passive lysis buffer, and 20 μL of the solution was used in the assay.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Luciferase assays were performed by using the dual luciferase reporter assay system (Promega) according to the manufacturer's protocol. Briefly, 10 μL of infected blood was harvested from the tail and subjected to erythrocyte lysis in 0.85% NH 4 Cl. The remaining cells were lysed in 50 μL of 1× passive lysis buffer, and 20 μL of the solution was used in the assay.…”
Section: Methodsmentioning
confidence: 99%
“…To establish synchronous infections in rats, whole blood was harvested from infected rats and then cultured for 16 h. Mature schizonts were purified from the cultures with Nicodenz (Axis-Shield PoC AS) and subsequently inoculated into rats. At 19 hpi, whole blood was harvested from the rats and subjected to erythrocyte-lysis in 0.85% NH 4 Cl. To kill the asexual stages, infected mice were treated with sulfadiazine for 2 d in their drinking water.…”
Section: Statistical Analysis Of Binding Motifmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to recognize and bind specific DNA motifs was confirmed for a number of Plasmodium and Cryptosporidium AP2s through protein-binding microarrays using recombinant proteins encompassing their respective AP2 DNA-binding domains (9). Furthermore, two putative AP2 transcription factors of Plasmodium appear to be essential for the development of mosquito invasive stages (10) and sporozoites (11,12), and the disruption of these genes was accompanied by altered transcript profiles. In addition, genes of the ookinetes, which defines the fertilized form of the malarial parasite in a mosquito's body, formed by fertilization of a macrogamete by a microgamete and developing into an oocyst, contain a conserved TAGCTA motif in the promoters of several genes whose transcription was affected by disruption of AP2-O gene (10).…”
mentioning
confidence: 99%
“…Studies in the rodent malaria species P. berghei have shown that the latter transition is regulated partly by posttranslational repression (72) and partly by a single AP2 transcription factor that activates many genes required for mosquito midgut invasion (110). It has also been shown that an AP2 factor is involved in sporozoite development (109) and that differentiation into gametocytes may be regulated by another translational repressor, PfPuf2 (36,78). These are the only two life cycle transitions for which underlying mechanisms have begun to emerge and it is not yet known whether epigenetic regulation plays a major role in any life cycle transition.…”
mentioning
confidence: 99%